Analisis Praktik Akad Istishna pada Jasa Konveksi dan Sablon di R.Industries Bogor - Farhan Zamzamy; Kholil Nawawi; Sofian Muhlisin (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2023)
This study aims to analyze the istishna contract in the convection and screen printing business of R. INDUSTRIES Bogor, as well as to explain the Muamalah Fiqh provisions in assessing the validity of the istishna contract in the convection and screen printing business of R. INDUSTRIES Bogor. This type of research is qualitative-descriptive research, using field research techniques, with direct observation and interviews with respondents namely one owner of clothing and screen printing services R. INDUSTRIES Bogor. The results of this study indicate that in general, istishna' contract transactions in the convection and screen printing business carried out by R. INDUSTRIES Bogor can be declared permissible or permissible. In a sense, transactions carried out are in accordance with the provisions of fiqh muamalah and do not contain elements that are are not permitted in muamalah fiqh, such as maysir, gharar, and usury. Keywords: istishna contract, fiqh muamalah, convection and screen printing